Survey on Enhanced Security Control measures in Cloud Computing systems - Abbas H.H.; Jaaz Z.A.; Albarazanchi I.; Abdulshaheed H.R. (IOP Publishing Ltd, 2023)
Application programs; Digital storage; Personal computers; Computing performance; Database management; Digital environment; Internet based; Private organizations; Remote storage; Security controls; Security measure; Storage as a service (STaaS)